Identification of Bacteria on Cockroach Feet (Periplaneta americana) in Resident Bay of Palu Permai and Sensitivity Test Against Antibiotics - I Nengah Kundera; Evasari Herman Sapu; Mursito Bialangi (TECHNO: JURNAL PENELITIAN, 2020)
Cockroaches (Periplaneta americana) a group of Arthropoda is living inside and outside the home because these animals can cause various diseases and act as vectors as well as hospes.  Cockroaches and other animals that act as vectors are strongly associated with the presence of microorganism pathogen carried on their feet. This study aims to identify the bacteria in Cockroach feet at Teluk Palu Permai residential neighborhood and the sensitivity test against antibiotics. This research is an exploratory laboratory, using a standard of bacteria isolation, Gram staining, Microbact system, and antibiotic sensitivity test. The results of the research were successful in identifying bacteria from Cockroaches, obtained from residential environments bacteria thas is Escherichia coli, Klebsiella pneumoniae, Proteus vulgaris, Salmonella arizonae, and Proteus mirabilis. The discovery of this bacteria is initial research that is useful for the development of handling infectious diseases transmitted by Cockroach vectors. This study has also found that bacteria experience resistance to the antibiotics Vancomycin, Chloramphenicol and Amoxycillin. While Ciprofloxacin and Ofloxacin antibiotics are still sensitive to Escherichia coli bacteria, Klebsiella pneumoniae, Proteus vulgaris, Salmonella arizonae, and Proteus mirabilis. This research is expected to provide preliminary data on the role of Cockroach as a vector of infectious diseases for humans caused by pathogenic bacteria and prevention efforts in the future.